Subtypes of constipation predominant irritable bowel syndrome based on rectal perception. Issue 3 (1st September 1998) - Harraf, F; Schmulson, M; Saba, L; Niazi, N; Fass, R; Munakata, J; Diehl, D; Mertz, H; Naliboff, B; Mayer, E A
Abstract : Background —Patients who complain of constipation can be divided into those who have lost the natural call to stool, but develop abdominal discomfort after several days without a bowel movement (no urge); and those who experience a constant sensation of incomplete evacuation (urge). Aims —To determine whether the two groups differ in symptoms, colonic transit, and perceptual responses to controlled rectal distension. Methods —Forty four patients with constipation were evaluated with a bowel symptom questionnaire, colonic transit (radiopaque markers), and rectal balloon distension. Stool (S) and discomfort (D) thresholds to slow ramp (40 ml/min) and rapid phasic distension (870 ml/min) were determined with an electronic distension device. Fifteen healthy controls were also studied. Results —All patients had Rome positive irritable bowel syndrome (IBS); 17 were no urge and 27 urge. Mean D threshold to phasic rectal distensions was 28 (3) mm Hg in no urge, 27 (3) mm Hg in urge (NS), but higher in the control group (46 (2) mm Hg; p<0.01). Sixty seven per cent of no urge and 69% of urge were hypersensitive for D. Slow ramp distension thresholds were higher in no urge (S: 26 (3); D: 45 (4) mm Hg) compared with urge (S: 16 (2); D: 31 (3) mm Hg; p<0.01), or with controls (S: 15 (1); D: 30 (3); p<0.01). Conclusions —Hyposensitivity to slow rectal distension is found in patients with IBS who complain of constipation and have lost the call to stool even though their sensitivity to phasic distension is increased.